Identification of new factors associated to walking impairment in patients with vascular-type claudication. (June 2019) - Mezdad, Tinhinan; Henni, Samir; Feuilloy, Mathieu; Chauvet, Pierre; Schang, Daniel; Abraham, Pierre
Objectives: Mechanisms of walking limitation in arterial claudication are incompletely elucidated. We aimed to identify new variables associated to walking limitation in patients with claudication. Methods: We retrospectively analyzed data of 1120 patients referred for transcutaneous exercise oxygen pressure recordings (TcpO2 ). The outcome measurement was the absolute walking time on treadmill (3.2 km/h, 10% slope). We used both: linear regression analysis and a non-linear analysis, combining support vector machines and genetic explanatory in 800 patients with the following resting variables: age, gender, body mass index, the presence of diabetes, minimal ankle to brachial index at rest, usual walking speed over 10 m (usual-pace), number of comorbid conditions, active smoking, resting heart rate, pre-test glycaemia and hemoglobin, beta-blocker use, and exercise-derived variables: minimal value of pulse oximetry, resting chest-TcpO2, decrease in chest TcpO2 during exercise, presence of buttock ischemia defined as a decrease from rest of oxygen pressure index ≤15 mmHg. We tested the models over 320 other patients. Results: Independent variables associated to walking time, by decreasing importance in the models, were: age, ankle to brachial index, usual-pace; resting TcpO2, body mass index, smoking, buttock ischemia, heart rate and beta-blockers for the linear regression analysis, and were ankle to brachial index, age, body mass index, usual-pace, decrease in chest TcpO2, smoking, buttock ischemia, glycaemia, heart rate for the non-linear analysis. Testing of models over 320 new patients gave r = 0.509 for linear and 0.575 for non-linear analysis (both p < 0.05). Conclusion: Buttock ischemia, heart rate and usual-pace are new variables associated to walking time.